Establishment of spruce plantations in native birch forests reduces soil fungal diversity. Issue 7 (31st May 2021) - Danielsen, Jørgen Skyrud; Morgado, Luis; Mundra, Sunil; Nybakken, Line; Davey, Marie; Kauserud, Håvard
ABSTRACT: Plantations of Norway spruce have been established well beyond its natural range in many parts of the world, potentially impacting native microbial ecosystems and the processes they mediate. In this study, we investigate how the establishment of spruce plantations in a landscape dominated by native birch forests in western Norway impacts soil properties and belowground fungal communities. Soil cores were collected from neighboring stands of planted spruce and native birch forests. We used DNA metabarcoding of the rDNA internal transcribed spacer 2 region and ergosterol measurements to survey the fungal community composition and its biomass, respectively. In the two investigated soil layers (litter and humus), fungal community composition, diversity and biomass were strongly affected by the tree species shift. Native birch stands hosted markedly richer fungal communities, including numerous fungi not present in planted spruce stands. In contrast, the spruce stands included higher relative abundance of ectomycorrhizal fungi as well as higher fungal biomass. Hence, establishing plantations of Norway spruce in native birch forests leads to significant losses in diversity, but increase in biomass of ectomycorrhizal fungi, which could potentially impact carbon sequestration processes and ecosystem functioning. Abstract : Establishing spruce plantations in native birch forest areas causes dramatic changes in belowground fungal communities.